2008
DOI: 10.1021/jp077663o
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Calorimetric Study of Orientationally Disordered Phases in Two Unusual Two-Component Systems

Abstract: In the present communication, investigations of two interesting (two-component) solid solutions are reported where one is a hydrogen (H-)-bonded pair and the other is a non-H-bonded pair. The former is the two-component system cyclooctanol (COOL) + cycloheptanol (CHOL), which forms a simple cubic phase [Rute, M. A.; Salud, J.; Negrier, P.; López, D. O.; Tamarit, J. Ll.; Puertas, R.; Barrio, M.; Mondieig, D. J. Phys. Chem. B 2003, 107, 5914]. This solid phase has been investigated at low temperatures and for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…which are also of interest to physicists working on glass transition phenomena. As shown in some of our recent publications, 37,38 the above said solid-solid transition can be supressed by addition of a second component which forms a solid solution with the first component. Although, the theoretical reasons responsible for the supression of this crystallization to rigid-crystalline phase are not yet understood; it never the less, led to a detailed study of the supercooled phases of the mixtures of these substances.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…which are also of interest to physicists working on glass transition phenomena. As shown in some of our recent publications, 37,38 the above said solid-solid transition can be supressed by addition of a second component which forms a solid solution with the first component. Although, the theoretical reasons responsible for the supression of this crystallization to rigid-crystalline phase are not yet understood; it never the less, led to a detailed study of the supercooled phases of the mixtures of these substances.…”
Section: Introductionmentioning
confidence: 87%
“…5. The a-process follows the critical power law [34][35][36][37][38][39] given by the equation below,…”
Section: Chxol + Npol Binary Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…6(A) shows at 148 K, the loss spectrum of the supercooled phase I (empty circles) together with the loss spectrum of phase III/ IV (full circles) at the same temperature. It seems to be obvious that the loss spectra of phase I present two additional relaxations besides the well-developed a-relaxation, denoted as b and c. Very recently, Singh et al [35] have published that only one additional relaxation, identified as c-relaxation, is present in phase I. The secondary b and c-relaxations of phase I are observed to persist in phase III/IV whereas the a-process is wholly suppressed, contrarily to what is reported in the work of Tyagi et al [20], in which phase III/IV displays a well-developped a-relaxation.…”
Section: Dielectric-losses Study In Dynamically Disordered Solid Statesmentioning
confidence: 99%
“…Several authors of the present work have recently undertaken a study of the dynamics of the OD mixed crystals formed between cC7‐ol and cC8‐ol 11. The motivation of such study was the findings previously found by the Murthy's group for some compositions of the cC7‐ol + cC8‐ol two‐component system, (cC7‐ol) 1− x (cC8‐ol) x 24. They found, in addition to the α ‐relaxation process, only one secondary relaxation ascribed to the conformations of the –OH group ( γ ‐relaxation), but no evidence of the β ‐relaxation.…”
Section: Introductionmentioning
confidence: 99%